Amino Acid Modifications During the Production (Shearing, Sterilization) of Plant-Based Meat Analogues: An Explorative Study Using Pet Food Production as an Example - Wehrmaker, Ariane M.; Zenker, Hannah; De Groot, Wouter; Sanders, Mark; Van Der Goot, Atze Jan; Janssen, Anja E. M.; Keppler, Julia; Bosch, Guido (ACS Food Science & Technology, 2022)
Shear cell technology is a promising method for the production of meat analogues. Meat analogues are also studied as alternative proteins for dogs and cats, which require high-quality protein. This study monitored the effect of shearing, using shear cell technology, and sterilization (26 min at 125.5 degrees C) on selected amino acids, advanced glycation end products (AGEs), lysinoalanine, o-phthalaldehyde-reactive lysine, as well as oxidation markers, free thiols, and dityrosine, in soy protein- and pea protein-based meat analogues. These are compared with animal-based pet foods. Processing resulted in modified amino acids, especially cysteine. Reductions in amino acid levels were higher in the soy-based meat analogue, but markers indicated more pronounced oxidation in the pea-based meat analogue. AGEs and lysinoalanine were not formed on shearing, only during sterilization. Despite extensive thermal treatment, the effects of processing on the protein quality of plant-based products were comparable or less than those in animal-based pet food.
CRIS-Team WoS Importer:2022-11-25